Voices from Coastal Communities: English Need Analysis of Local Tour Guide - Giovanni Oktavinanda; Endah Anisa Rahma; Asri Mursawal; Veni Nella Syahputri (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2022)
Tourists' demands which particularly those of international visitors are best served by tour guides, who are valuable coastal human resources. English as an international language is essential for communicating with travelers and is a crucial communication ability in the travel and tourism sector. Thence, it is necessary to analyze the English needs of local tour guides on the Simeulue coast. There were ten local tour guides chosen through random sampling as the subjects. The research instrument was a questionnaire set adapted from Prachanant (2012) address needs, functions, and issues with the use of English. It also makes reference to elements from the need analysis model developed by Waters & Hutchinson (1987).Interactive Analysis by Miles, Huberman, and Saldana (2014) was used to perform additional analysis on the findings, and the results were later displayed and verified. The results revealed that speaking was the most important English skill for the participants, followed by listening, reading, and writing. Second, individuals felt they lacked proficiency in speaking, listening, writing, and reading. Therefore, they desired to develop their speaking, listening, writing, and reading abilities. It implied that speaking played a major role in tour guiding and needs further follow-ups.